X-ray structures of organic salts between diethanolamine and ortho- and para-isomers of aminobenzoic acid: A specific synthon responsible for an association of the components - Ibragimov, Aziz Bakhtiyarovich; Zakirov, Bakhtiyar Sabirkhanovich; Ibragimov, Bakhtiyar Tulyaganovich; Ashurov, Jamshid Mengnorovich (European Journal of Chemistry, 2018)
Two organic salts between diethanolamine (DEA) and ortho- and para-isomers (OABA and PABA) of aminobenzoic acid (ABA) have been obtained and their X-ray single crystal structures determined. In both salts, cationic and anionic components are incorporated into dimers by the two H-bonds formed between ABA carboxylate oxygen atoms and nitrogen and one of oxygen atoms of DEA which close a cycle with the graph-set notation of R22(9). Further dimers are associated by intricate systems of the H-bonds into 1D- and 3D-network structures in crystals of DEA·OABA and DEA·PABA, respectively. H-bonding which generates these dimers may be considered as a synthon specific for yielding of salts between DEA and mono-substituted aromatic benzoic acids.